Genetically Predicted Differences in Systolic Blood Pressure and Risk of Cardiovascular and Noncardiovascular Diseases: A Mendelian Randomization Study in Chinese Adults. Issue 3 (5th January 2023) - Clarke, Robert; Wright, Neil; Walters, Robin; Gan, Wei; Guo, Yu; Millwood, Iona Y.; Yang, Ling; Chen, Yiping; Lewington, Sarah; Lv, Jun; Yu, Canqing; Avery, Daniel; et al.
Abstract : Background: Mendelian randomization studies of systolic blood pressure (SBP) can assess the shape and strength of the associations of genetically predicted differences in SBP with major disease outcomes and are less constrained by biases in observational analyses. This study aimed to compare the associations of usual and genetically predicted SBP with major cardiovascular disease (CVD) outcomes, overall and by levels of SBP, age, and sex. Methods: The China Kadoorie Biobank involved a 12-year follow-up of a prospective study of 489 495 adults aged 40 to 79 years with no prior CVD and 86 060 with genetic data. Outcomes included major vascular events (59 490/23 151 in observational/genetic analyses), and its components (ischemic stroke [n=39 513/12 043], intracerebral hemorrhage [7336/5243], and major coronary events [7871/4187]). Genetically predicted SBP used 460 variants obtained from European ancestry genome-wide studies. Cox regression estimated adjusted hazard ratios for incident CVD outcomes down to usual SBP levels of 120 mm Hg. Results: Both observational and genetic analyses demonstrated log-linear positive associations of SBP with major vascular event and other major CVD types in the range of 120 to 170 mm Hg. Consistent with the observational analyses, the hazard ratios per 10 mm Hg higher genetically predicted SBP were 2-fold greater for intracerebral hemorrhage (1.71 [95% CI, 1.58–1.87]) than for ischemic stroke (1.37 [1.30–1.45]) or major coronary event (1.29 [1.18–1.42]). Genetic analyses also demonstrated 2-fold greater hazard ratios for major vascular event in younger (1.69 [95% CI, 1.54–1.86]) than in older people (1.28 [1.18–1.38]). Conclusions: The findings provide support for initiation of blood pressure-lowering treatment at younger ages and below the conventional cut-offs for hypertension to maximize CVD prevention, albeit the absolute risks of CVD are far greater in older people.